Crustaceans (shrimp, crab, and lobster): A comprehensive review of their potential health hazards and detection methods to assure their biosafety. Issue 1 (14th November 2022) - Farag, Mohamed A.; Mansour, Somaia T.; Nouh, Roua A.; Khattab, Amira R.
Abstract: Crustaceans are popular seafood items worldwide owing to their rich nutritional value, unique tastes, and their incorporation in a variety of cuisines. There has been a great concern about the safety of crustaceans for human consumption being more prone to hazardous contaminants due to their exposure to diverse habitats and unhealthy farming and handling practices. These hazards can arise from chemical contaminants such as heavy metals, environmental pollutants, and biotoxins or biological sources, that is, pathogenic microbes and parasites. The different types of chemical contamination of crustaceans as well as biological hazards are reviewed as major part of this review. Although there are many reviews on contaminants in fisheries, nothing is traces to crustaceans. The current review compiles the food safety hazards of crustaceans arising from both chemical and biological origins and their impact on human health in farmed versus wild origins. The different methods of contaminants detection, viz. microbiological, molecular, and analytical methods, as well as control measures viz. cooking and processing methods that can be implemented to safeguard consumer safety are also reviewed. Future perspectives have been raised toward HACCP protocol implementation during handling, processing, and storage of crustaceans and posing real‐time freshness monitoring tools such as intelligent packaging. Abstract : Food safety hazards of crustaceans arising from chemical and biological contaminants, their control measures and detection me